Facile Synthesis of AuPd Nanochain Networks on Carbon Supports and Their Application as Electrocatalysts for Oxygen Reduction Reaction. Issue 4 (26th February 2014) - Cha, Areum; Shim, Jun Ho; Jo, Ara; Lee, Sang Cheol; Lee, Youngmi; Lee, Chongmok
Abstract The present work reports the facile synthesis and characterization of carbon‐supported porous Pd shell coated Au nanochain networks (AuPdNNs/C). By using Co nanoframes as sacrificial templates, AuPdNNs/C series have been prepared by a two‐step galvanic replacement reaction (GRR) technique. In the first step, the Au metal precursor, HAuCl4, reacts spontaneously with the formed Co nanoframes through the GRR, resulting in Au nanochain networks (AuNNs). The second GRR is performed with various concentrations of Pd precursor (0.1, 1, and 10 mM PdCl2), resulting in AuPdNNs/C. The synthesized AuPdNNs/C series are investigated as electrocatalysts for oxygen reduction reaction (ORR) in alkaline solution. The physical properties of the AuPdNNs/C catalysts are characterized by scanning electron microscopy (SEM), high‐resolution transmission electron microscopy (HRTEM), UV‐vis absorption spectroscopy, and cyclic voltammetry (CV). Rotating disk electrode (RDE) voltammetric studies show that the Au0.8Pd0.2NNs/C (prepared using 1 mM PdCl2) has the highest ORR activity among all the AuPdNNs/C series, which is comparable to commercial Pt catalyst (E‐TEK). The ORR activity of AuPdNNs/C is presumably due to the enhanced Pd surface area and high porosity of Pd nanoshells.